2010
DOI: 10.1186/1744-8069-6-89
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Inflammation Activates Glial and Immune Cells in Both the Trigeminal Ganglia and in the Spinal Trigeminal Nucleus

Abstract: BackgroundGlial cells have been shown to directly participate to the genesis and maintenance of chronic pain in both the sensory ganglia and the central nervous system (CNS). Indeed, glial cell activation has been reported in both the dorsal root ganglia and the spinal cord following injury or inflammation of the sciatic nerve, but no data are currently available in animal models of trigeminal sensitization. Therefore, in the present study, we evaluated glial cell activation in the trigeminal-spinal system fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 71 publications
(133 reference statements)
4
106
0
Order By: Relevance
“…Despite the detection of P2Y 12 mRNA in total mouse TG and of functional protein on a limited percentage of SGCs in culture [37], surprisingly no P2Y 12 immunostaining was detected on TG sections-a finding which suggested that the receptor protein is not expressed within the ganglion, but in the boundary area with the trigeminal nerve [80]. Interestingly, a recent study demonstrates the involvement of glial P2Y 12 receptor subtype in trigeminal neuropathic pain.…”
Section: Satellite Glial Cells In Sensory Gangliamentioning
confidence: 89%
See 1 more Smart Citation
“…Despite the detection of P2Y 12 mRNA in total mouse TG and of functional protein on a limited percentage of SGCs in culture [37], surprisingly no P2Y 12 immunostaining was detected on TG sections-a finding which suggested that the receptor protein is not expressed within the ganglion, but in the boundary area with the trigeminal nerve [80]. Interestingly, a recent study demonstrates the involvement of glial P2Y 12 receptor subtype in trigeminal neuropathic pain.…”
Section: Satellite Glial Cells In Sensory Gangliamentioning
confidence: 89%
“…The key role of SGCs in the development and maintenance of chronic pain has been demonstrated by their increased expression and release of IL-1β [77], TNFα [62], as well as by the increased gap junctionmediated cell coupling [78,79] following nerve injury. Like other glial cells, SGCs also respond to nerve injury by up-regulating the expression of glial fibrillary acidic protein (GFAP) and undergoing division in response to chronic pain [77,80]. Altogether, these changes lead to increased excitability of both primary afferents and CNS neurons, and the development of hyperalgesia and allodynia [81].…”
Section: Satellite Glial Cells In Sensory Gangliamentioning
confidence: 99%
“…The interaction between immune/glial cells and neurons during the induction of chronic pain is a novel concept that has gained much attention in the last years. For instance, during peripheral inflammation, the increase in neuronal inputs from the periphery to the CNS results in an intense activation of glial cells (microglia and astrocytes), mainly at the spinal cord and trigeminal nucleus (19)(20)(21). These cells then produce and release a great number of substances, including proinflammatory cytokines (TNF-α and IL1-β), which directly or indirectly act upon the neurons of the nociceptive system to amplify the pain process (7).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that primary cultures of trigeminal ganglia recapitulate the main characteristics of in situ ganglia and can be used as a model to explore the molecular mechanisms of nociception [4,8]. Hence, we exploited the use of lipopolysaccharide (LPS), a canonical inflammatory agent [12] that rapidly activates ionized calcium binding adaptor molecule 1 (Iba1)-immunopositive macrophages [13] with production of their major inflammatory cytokine TNFα in dorsal root ganglia (DRG) in vivo and in vitro [14] and in basal ganglia [15]. The aim was to clarify if LPS application could differentially affect macrophage presence, TNFα release, and P2X3 receptormediated currents in trigeminal ganglion cultures from wild type (WT) and R192Q KI ganglia.…”
Section: Introductionmentioning
confidence: 99%